Descrição do girino de Odontophrynus Salvatori (Anura, Leptodactylidae) - Brandão, Reuber Albuquerque (2000)
The tadpole of Odontophrynus salvatori Caramaschi, 1996 is described from Chapada dos Veadeiros, State of Goiás, Brazil. The tadpole resembles those of the genus Proceratophrys Miranda-Ribeiro, 1920, mostly by depressive body in lateral view, small body size, and habitat use.